Analisis Moderasi Leverage Terhadap Pengaruh Risiko Keuangan pada ROE Perbankan di BEI - Afifah Oktavia; Rosyeni Rasyid (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study examines the impact of financial risks—namely credit risk (Non-Performing Loan/NPL), liquidity risk (Loan to Deposit Ratio/LDR), and market risk (Net Interest Margin/NIM)—on financial performance measured by Return on Equity (ROE) among banks listed on the Indonesia Stock Exchange (IDX). Additionally, it investigates the moderating role of leverage (Debt to Equity Ratio/DER) on the relationship between financial risks and financial performance. The methodology employed is panel data regression using the Random Effect Model (REM) and Moderated Regression Analysis (MRA). The results reveal that liquidity risk (LDR) has a significant negative effect on ROE, while market risk (NIM) has a positive and significant effect, and credit risk (NPL) does not exhibit a significant partial effect on ROE. Leverage significantly moderates the negative effect of liquidity risk on ROE but does not moderate the effects of credit risk and market risk on ROE These findings underscore the importance of liquidity management and capital structure in maintaining bank profitability amid dynamic financial risks. Furthermore, the low coefficient of determination suggests the need for further research incorporating additional variables such as banking digitalization and macroeconomic factors to gain a more comprehensive understanding of the determinants of financial performance in Indonesian banks.